Interleukin 21-Armed EGFR-VHH-CAR-T Cell Therapy for the Treatment of Esophageal Squamous Cell Carcinoma - Chenglin Zhang; Yanyan Liu; Haoran Guo; Ying Peng; Lei Huang; Shuangshuang Lu; Zhimin Wang (Biomedicines)
Background/Objectives: Esophageal squamous cell carcinoma (ESCC) is a common form of esophageal cancer with a poor prognosis and limited treatment options. Epidermal growth factor receptor (EGFR), an overexpressed oncogenic gene in all ESCC patients, is an attractive target for developing therapies against ESCC. There is an extremely urgent need to develop immunotherapy tools targeting EGFR for the treatment of ESCC. Methods: In this study, we developed human Interleukin-21 (hIL-21)-armed, chimeric-antigen-receptor-modified T (CAR-T) cells targeting EGFR as a new therapeutic approach. The CAR contains a variable domain of the llama heavy chain of heavy-chain antibodies (VHHs), also known as nanobodies (Nbs), as a promising substitute for the commonly used single-chain variable fragment (ScFv) for CAR-T development. Results: We show that nanobody-derived, EGFR-targeting CAR-T cells specifically kill EGFR-positive esophageal cancer cells in vitro and in animal models. Human IL-21 expression in CAR-T cells further improved their expansion and antitumor ability and were observed to secrete more interferon-gamma (IFN-γ), tumor necrosis factor alpha (TNF-α), and Interleukin-2 (IL-2) when co-cultured with ESCC cell lines in vitro. More CD8+ CAR-T cells and CD3+CD8+CD45RO+CD62L+ central memory T cells were detected in CAR-T cells expressing hIL-21 cells. Notably, hIL-21-expressing CAR-T cells showed superior antitumor activity in vivo in a KYSE-150 xenograft mouse model. Conclusions: Our results show that hIL-21-armed, nanobody-derived, EGFR-specific CAR-T cell therapy is a highly promising option for treating ESCC patients.